Interesting cases of aspirated foreign bodies: Review articles - Tawfique, Saleh A. (Zanco Journal of Medical Sciences (ZJMS), 2016)
Five cases of rare and interesting foreign bodies are reported. Their presentation, difficulties in diagnosis, management and possible complications are discussed. These cases were seen in Al-Ain Hospital, ENT Department, UAE. All were diagnosed and managed by the author of this paper at variable dates. The aim of this publication is to report on rare inhaled foreign bodies, which is not seen often and to report on the difficulty in diagnoses of certain foreign bodies. It is advisable that rigid bronchoscopy be performed under general anaesthesia for all cases of highly suspicious for aspirated foreign bodies, for cases with chronic long lasting cough and in children with wheezy chest of unclear causes who do not response to medical therapy.